Evaluasi Efek Geopolitik: Analisis Abnormal Return dan Trading Volume pada IDX30 Pasca Peristiwa Konflik Rusia dan Ukraina - I Made Adi Jaya; Mahanavami Gusti Ayu; I Wayan Tantra; Wiryawan Suputra Gumi; I Nyoman Parta (KRISNA: Kumpulan Riset Akuntansi, 2024)
The capital market is a dynamic arena, influenced by various factors that can cause fluctuations in securities prices. Among these many factors, information has a significant role in influencing securities prices, especially shares. This research aims to examine the differences in average abnormal returns and average trading volume activity before and after the Russian and Ukrainian conflict on February 24 2022, especially in companies listed as members of the IDX30 index on the Indonesia Stock Exchange. The research method used is event study with a comparative quantitative approach. The research period involved 15 trading days, consisting of 7 days before the event (t-7), the day of the event (t-0), and 7 days after the event (t+7) of the declaration on February 24 2022. Hypothesis testing was carried out using paired tests sample t-test for the abnormal return variable and the Wilcoxon signed rank test for the trading volume activity variable. The results of hypothesis testing show that the average abnormal return does not have a significant influence on the conflict between Russia and Ukraine, while the average trading activity volume has a significant influence on the conflict. However, there is no significant difference in abnormal returns, while there is a significant difference in volume trading activity before and after the Russian and Ukrainian conflict. These findings contribute to understanding the impact of geopolitical events on capital markets and provide insights for investors and financial practitioners.